The life of richard wagner : 1848-1860 - Newman, Ernest (NewYork : Cambridge university press, 2014)
Ernest Newman's four-volume Life of Wagner, originally published between 1933 and 1947, remains a classic work of biography. The culmination of forty years' research on the composer and his works (Newman's first Study of Wagner was first published in 1899), these books present a detailed portrait of perhaps the most influential, the most controversial and the most frequently reviled composer in the whole history of western music. Newman was aware that no biography can ever claim to be complete or completely accurate: 'The biographer.
Includes bibliographical references and index.
Keywords: Music